The genus Ampittia in Africa with the description of a new species (Hesperiinae; Aeromachini) and three new species in the genera Andronymus and Chondrolepis (Hesperiinae, incertae sedis) (Lepidoptera; Hesperiidae) - Larsen, Torben B.; Congdon, T. C. E. (Zootaxa, 2012)
The genus Ampittia Moore, 1882 is accepted as a valid genus occurring in both Africa and Asia on the basis of a number ofunusual shared characters, a somewhat surprising result since we had expected to describe a new genus. The species A. kilo-mbero sp. nov. from Tanzania is described as the third African member of the genus. Andronymus fontainei sp. nov. isdescribed from the DRC as a probable endemic of the Albertine Rift. Chondrolepis ducarmei sp. nov. is a submontane speciesthat is certainly endemic to the Albertine Rift. Chondrolepis uluguru sp. nov. is a submontane species from the Uluguru Moun-tains in Tanzania; it is yet another endemic of the Eastern Arc Mountains that are one of the most urgent conservation concerns in Tanzania.